I@m pro4u - Zulkhairi, Insyirah Ahmad; Salleh, Nor Asneyra Edayu; Daud, Mohd Shamsul (Universiti Teknologi MARA, Kedah, 2019)
Students pursuing their study to tertiary education require a high level of information literacy. However, the strings are different when students come in different levels of literacy. Due to this scenario, the I@M Pro4U is designed specifically for educators regardless of school, university and the public. This platform uses a relaxing tutorial method but covers important aspects to know, share and exchange among those who involve in this information business